The real story about food safety - Kastner, Curtis L. (American Society of Animal Science, 2008)
Students should be thoroughly aware of the safety issues that affect the food industry and we should be prepared to summarize the issues in our classes. Food safety covers areas including nutrition, chemical residues, physical contaminants, and food-borne diseases. The real and perceived issues relating to each of these areas are summarized along with thoughts of how to address those issues. The information could be used to initiate classroom discussions about food safety and enhance understanding.
Keywords: Food science; Food; Teaching; Chemicals; Pathogens; Safety